Association of Internet Addiction with Social Support, Loneliness And Stress: A Cross Sectional Study among Female College Students (Indian Journal of Public Health Research & Development, 2020)
Background: Internet Addictionis a significant emerging mental health condition among Indian collegestudents and cascading into a major public health concern. Internet addiction has witnessed an upsurge asa clinical phenomenon among young adults precipitated by new challenges specific to this developmentalage and owing to its complexity resulting from multiple psychosocial factors which warrants the need foreffective multi modal intervention due to high relapse rates and resistance to treatment.Aim: The present investigation was aimed to evaluate the association of Internet Addiction with socialsupport, loneliness and stress among female college students in Chandigarh.Methodology: It was a cross sectional study among 200 undergraduate female students within the agerange of 18-21 years, drawn from various colleges pertaining to Chandigarh region. Internet Addiction Test(Young, 1998) was employed as a screening instrument to identify internet dependence and other assessmenttools administered include Perceived Stress Scale, Multidimensional Perceived Social Support scale andUCLA Loneliness Scale.Results: Comparative Analysis revealed that there were significant differences between Internet Addictionand Non Internet Addiction groups of female college students in the areas of Stress, Loneliness and FamilySupport. Bivariate correlation analysis showed a positive relationship of Internet Addiction with Stress andLoneliness. However there emerged a negative correlation between Internet Addiction and Family Support.Conclusion: Our study holds heuristic value for elucidating the potential impact of low family supportand heightened stress due to plethora of reasons may increase vulnerability to Internet Addiction amongfemale college students. We can conclude that young adults with insufficient or conflictual family interactiontriggers emotional loneliness resulting in either social withdrawal or search for needed relationships inthe Internet environment. Hence, family support is an important factor in treating and preventing Internetaddiction.
Keywords: Internet Addiction, Stress, Loneliness, Social Support, College Students.